2012
DOI: 10.1152/jn.00390.2011
|View full text |Cite
|
Sign up to set email alerts
|

Coding of sound direction in the auditory periphery of the lake sturgeon,Acipenser fulvescens

Abstract: Meyer M, Popper AN, Fay RR. Coding of sound direction in the auditory periphery of the lake sturgeon, Acipenser fulvescens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The work on modern fishes described above provides a framework for how the auditory systems of these early aquatic tetrapods could have been organized. Although most of the physiological data on directional hearing come from teleosts, the data are consistent with anatomical and physiological results from other taxonomically distant fishes [McCormick 1999; Meyer, 2010, 2012] and thus may reflect the organization of the auditory systems of the early aquatic tetrapods [Carr and Christensen-Dalsgaard, 2016]. It seems unlikely that neural circuits sensitive to sound in air appeared de novo because sound sensitivity would have been based on the same auditory end organs as in the ancestors.…”
Section: The Transition Onto Land: Early Tetrapodssupporting
confidence: 66%
See 1 more Smart Citation
“…The work on modern fishes described above provides a framework for how the auditory systems of these early aquatic tetrapods could have been organized. Although most of the physiological data on directional hearing come from teleosts, the data are consistent with anatomical and physiological results from other taxonomically distant fishes [McCormick 1999; Meyer, 2010, 2012] and thus may reflect the organization of the auditory systems of the early aquatic tetrapods [Carr and Christensen-Dalsgaard, 2016]. It seems unlikely that neural circuits sensitive to sound in air appeared de novo because sound sensitivity would have been based on the same auditory end organs as in the ancestors.…”
Section: The Transition Onto Land: Early Tetrapodssupporting
confidence: 66%
“…The directional response properties of nVIII afferents have been assessed only in the lake sturgeon ( Acipenser fulvescens) [Meyer et al 2010, 2012]. Primary auditory afferents in the posterior ramus of nVIII (after the convergence of afferents from the saccule, lagena, and macula neglecta) responded to low frequencies (100–300 Hz), exhibited phase locking to the sinusoidal stimuli, and had the characteristic cosine directional response pattern of hair cells and primary afferents found in teleost fishes (fig.…”
Section: Directional Hearing In Osteichthyesmentioning
confidence: 99%
“…Michaela pointed out that the Fay shaker table represents a carefully controlled stimulus device simulating water particle motion. This work showed that peripheral coding mechanisms for spatial and spectral analysis of sound in sturgeon appear similar to those of teleost fish, such as the goldfish (Meyer et al, 2010;Meyer et al, 2012).…”
Section: Hearing In Vertebrates: a Psychophysical Databookmentioning
confidence: 69%
“…The sensory role of the inner ear endorgans can be vestibular and/or auditory, depending on the response frequencies and how the brain uses the information encoded in the VIIIth nerve afferents that project into the first order octaval nuclei in the brainstem (McCormick, 1999). The saccule has been described as the main auditory endorgan in teleost fishes (Brown et al, 2019;Coffin et al, 2012;Ladich and Schulz-Mirbach, 2016;Lu and DeSmidt, 2013;Smith et al, 2011), although the auditory sensitivity of utricle (Denton and Gray, 1979;Lu et al, 2004;Rogers and Sisneros, 2020) and lagena (Lu et al, 2003;Meyer et al, 2012;Sand, 1974;Vetter et al, 2019) has also been reported in a few species.…”
Section: Introductionmentioning
confidence: 99%